2016
DOI: 10.1007/s00213-016-4369-8
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine and neuroactive steroid combinations in rats: anxiolytic-like and discriminative stimulus effects

Abstract: Although drug interactions depended on the constituent drugs, the combination tested, and the behavioral endpoint; a combination was identified that would be predicted to result in supra-additive anxiolytic-like effects with predominantly additive discriminative stimulus effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…MDZ is an allosteric agonist of synaptic GABA-A receptors through sites distinct from the neurosteroid binding site (Nusser et al, 1997). A previous study has shown that the combination of GX and MDZ exerts synergistic anxiolytic effects (Gunter et al, 2016). In the present study, we found that neurosteroid exerts a synergistic response with MDZ on GABA-A receptors.…”
Section: Discussionsupporting
confidence: 67%
“…MDZ is an allosteric agonist of synaptic GABA-A receptors through sites distinct from the neurosteroid binding site (Nusser et al, 1997). A previous study has shown that the combination of GX and MDZ exerts synergistic anxiolytic effects (Gunter et al, 2016). In the present study, we found that neurosteroid exerts a synergistic response with MDZ on GABA-A receptors.…”
Section: Discussionsupporting
confidence: 67%
“…Anesthetic steroids potentiate the actions of the intravenous anesthetics propofol and etomidate in electrophysiological 8 and behavioral assays 9 , 31 . Similarly, coapplication of neuroactive steroids enhances the anxiolytic effect of the benzodiazepine triazolam 32 , 33 and the anticonvulsant potency of diazepam against seizures induced by pentylenetetrazol 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Deviation from a linear isobole of additivity, typically interpreted as synergy, has been observed in the modulation of GABA-activated a1b2g2L receptors by the combination of propofol and flurazepam (Reynolds and Maitra, 1996), the enhancement of [ 3 H]diazepam binding to cerebrocortical synaptoneurosomes by the combination of GABA and pentobarbital, the enhancement of [ 3 H]muscimol binding by pentobarbital and diazepam (DeLorey et al, 1993), and the production of loss-of-righting in rats by combinations of barbiturates and benzodiazepines (DeLorey et al, 1993). Superadditive anxiolytic effects have been found for certain concentration combinations of triazolam and pregnanolone and for clonazepam and ganaxalone in the elevated zero maze assay (Gunter et al, 2016). In patients, the combination of midazolam and propofol apparently synergistically produces a loss of response to command (McClune et al, 1992;Minto et al, 2000).…”
Section: Discussionmentioning
confidence: 99%